Epidemiology of Shigella, Salmonella, and Campylobacter among diarrheic under-five-year-old children in central Ethiopia - Tizazu Zenebe; Ermiyas Endewunet; Aminu Seman; Tadesse Eguale; Tamrat Abebe (Journal of Infection in Developing Countries)
Introduction: Diarrheagenic bacteria are among the major contributors to the global diarrheal burden. The absence of up-to-date data on the etiologies of diarrhea due to limited active surveillance and clinical laboratory capacity makes the burden more severe. Shigella, Salmonella, and Campylobacter are among the most common bacterial etiologies of childhood diarrhea. The present study aimed to provide epidemiological data on these bacterial etiologies in under-five-year-old children in Ethiopia.